Las Heliantheae endémicas a México: una guía hacia la conservación - Villaseñor, Jose Luis (Instituto de Ecología, A.C., 1991)
México is the most important center of diversification of the tribe Heliantheae (Asteraceae). Recent estimates indícate the occurrence of about 1,150 species of Heliantheae in México, 740 of them being endemic. Analysis of range distribution of such endemic species shows the existence of areas with largeconcentration of species, which should be considered when setting aside future natural protected areas. This analysis also points out the role played by endemism in the programs tending toward conservation of biotic richness.